Factors Influencing Quality of Life for Disabled and Nondisabled Elderly Population: The Results of a Multiple Correspondence Analysis. (26th June 2013) - Avolio, M.; Montagnoli, S.; Marino, M.; Basso, D.; Furia, G.; Ricciardi, W.; de Belvis, A. G.
Abstract : Objectives . The aim of our study is to examine the role of some factors (sociodemographic patterns, social relationship support, and trust in healthcare actors) on structure of quality of life among the Italian elderly population, by stratifying according to presence or absence of disability. Methods . Using data of the Italian National Institute of Statistics (ISTAT) survey, we obtained a sample of 25, 183 Italian people aged 65+ years. Multiple Correspondence Analysis (MCA) was used to test such a relationship. Results . By applying the MCA between disabled and nondisabled elderly population, we identified three dimensions: "demographic structure and social contacts, " "social relationships, " "trust in the Italian National Health Services (INHS)." Furthermore, the difference in trust on the INHS and its actors was seen among disabled and non-disabled elderly population. Conclusions . Knowledge on the concept of quality of life and its application to the elderly population either with or without disability should make a difference in both people's life and policies and practices affecting life. New domains, such as information and trusting relationships both within and towards the care network's nodes, are likely to play an important role in this relationship.